Comparison of Anal Versus Rectal Staging in the Prognostication of Rectal Squamous Cell Carcinoma: A Population-Based Analysis. Issue 3 (March 2019) - Goffredo, Paolo; Robinson, Timothy J.; Frakes, Jessica M.; Utria, Alan F.; Scott, Aaron T.; Hassan, Imran
Abstract : BACKGROUND: Rectal squamous cell carcinoma is a rare malignancy with limited data regarding management and prognosis. It is also unknown whether a rectal squamous cell cancer staging system should be based on size, as for anal squamous cell carcinoma, or depth of invasion, as for rectal adenocarcinoma. OBJECTIVE: The aims of the current study were to determine the optimal management strategy, prognostic factors, and staging system for rectal squamous cell carcinoma. DESIGN: This was a population-based study. SETTINGS: The Surveillance, Epidemiology, and End Results database was used to identify patents diagnosed between 1988 and 2013. PATIENTS: Patients ≥18 years of age undergoing radiation or local excision alone, radiation with local excision, or radiation with radical resection were included. Patients were then staged according to both the American Joint Committee on Cancer classification for rectal adenocarcinoma (American Joint Committee on Cancer-rectum) and anal cancer (American Joint Committee on Cancer-anus). MAIN OUTCOME MEASURES: The main outcome was 5-year, disease-specific survival. RESULTS: In both univariate and multivariate survival analyses, the addition of local excision or radical resection to radiation resulted in similar-to-worse outcomes across all of the stages. Among patients staged according to American Joint Committee on Cancer-rectum (n = 1646), although a significant difference in 5-year survival was observed for stage I as compared with higher stages, no difference was noted between stages II and III (80% vs 61% and 62%). However, in the American Joint Committee on Cancer-anus classification (n = 1327), a significant difference was observed across all of the stages (87% vs 72% vs 59%; p < 0.001). In multivariate analysis, the prognostic discrimination based on HRs provided by the American Joint Committee on Cancer-anus was superior to that of the American Joint Committee on Cancer-rectum. LIMITATIONS: This study was limited by lack of data on chemotherapy and location of positive nodes. CONCLUSIONS: A treatment approach primarily based on radiation should be considered the optimal management strategy for rectal squamous cell carcinoma. Moreover, a staging system based on size (American Joint Committee on Cancer-anus) rather than on depth of invasion (American Joint Committee on Cancer-rectum) appears to be more accurate in predicting its prognosis. SeeVideo Abstract athttp://links.lww.com/DCR/A734 .